ANALISIS VISUAL DESAIN KARAKTER FAUST PADA GAME “MY LOVELY DAUGHTER” MENGGUNAKAN METODE MANGA MATRIX - Fitriadi Putri, Tiara Andhienia (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2024)
Video games are a popular entertainment phenomenon among people today. Various genres of video games have sprung up and have their own impression on the players. In it, video games have visual elements that have their own uniqueness and aesthetic value. These visuals can provide information, especially on character design in the game world. Like the visual elements in the game